Proposal for the Creation of a National Strategy for Precision Medicine in Cancer: a position statement of SEOM, SEAP and SEFH - Ruth Vera; José Palacios; Xavier Matías-Guiu; Miguel Martín; María Jesús Lamas; Enrique de Álava; Miguel Ángel Calleja; Azucena Aldaz; Pilar Garrido (Farmacia Hospitalaria)
Precision medicine is an emerging approach for disease treatment and prevention that takes into account individual variability in genes, environment, and lifestyle for each person. Precision medicine is transforming clinical and biomedical research, as well as health care itself from a conceptual, as well as a methodological viewpoint, providing extraordinary opportunities to improve public health and lower the costs of the healthcare system. However, the implementation of precision medicine poses ethical-legal, regulatory, organizational and knowledge-related challenges. Without a national strategy, precision medicine, which will be implemented one way or another, could take place without the appropriate planning that can guarantee technical quality, equal access of all citizens to the best practices, violating the rights of patients and professionals and jeopardizing the solvency of the healthcare system. With this paper from the Spanish Societies of Medical Oncology (SEOM), Pathology (SEAP), and Hospital Pharmacy (SEFH) we highlight the need to institute a consensual national strategy for the development of precision medicine in our country, review the national and international context, comment on the opportunities and challenges for implementing precision medicine, and outline the objectives of a national strategy on precision medicine in cancer.